Cultural elements in Malaysian printmaking: a case study of Chinese printmakers’ artworks from 1950 to 1989 - Muhamad, Noor A’yunni (2025)
Diverse races, ethnicities, and unique cultures plays a significant role as the foundation Malaysia. Culture plays a vital role in shaping the nation, thus, Malaysian cultural elements (MCE) must be recognised, understood, and applied across society. However, in the visual arts, particularly printmaking, MCE are less emphasised through visual representation. This research aims to identify the characteristics of MCE portrayed in printmaking artworks produced by Chinese printmakers between 1950 and 1989, offering insight into Malaysian culture from a visual perspective. The objective of this research are: (1) to identify MCE through policies and official documents, (2) to analyse the visual representation in selected Malaysian Chinese printmaking artwork based on MCE (from objective One), and (3) to synthesise the Malaysian cultural elements (Objective One) and visual representation portrayed by Chinese printmaking artists (Objective two) for proposing a new MCE framework for visual arts. Using a qualitative intrinsic case study approach, the first objective was achieved through document analysis of policies and official documents, producing a comprehensive list of MCE. The second objective involved artefact observation of 44 selected printmaking artworks to examine the visual representations depicted in the artworks. The synthesis of both findings developed MCE framework for visual arts, through an iterative process thus achived the objective three. Findings from document analysis identified 5 material cultural elements with 18 sub-elements, and 33 non-material cultural elements with 33 sub-elements. Visual analysis revealed 24 categories of visual representation linked to the MCE. The proposed framework incorporates subjects, form, context, and content to guide the recognition and understanding of cultural elements in visual arts.